IMPROVING THE STUDENTS’ WRITING SKILL THROUGH ROUNDTABLE TECHNIQUE - Setiadi, Astrianto (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2015)
This research aimed to explain the improvement of the students’ writing in terms of content dealing with unity and completeness and organization dealing with vocabulary. To explain the improvement, the researcher used a classroom action research (CAR) which was conducted in two cycles in which every cycle consisted of four meetings. The location of this research was taken at the second year students of SMP Muhammadiyah 5 Mariso, Makassar with a number of the subject were 30 students. The research findings indicated that the application of Roundtable Technique was significant in improving the students’ writing ability in terms of content and organization. It was proved by the mean score of cycle I was 63.75. It was classified as fair then improved to be 78.16. It was classified as good in cycle II. They are higher than the mean score of diagnostic test namely 50.70 that classified as poor. Therefore there was the improvement of the students’ writing ability in terms of content dealing with unity and completeness and organization dealing with vocabulary.